Quiste dentígero asociado con un diente ectópico en el seno maxilar: Reporte de un caso y revisión de la literatura - Antunes Freitas, D.; Vergara Hernández, C. I.; Díaz Caballero, A.; Comino Mol, V.; Ferreti Bonan, P. R. [UNESP] (SciELO Espana/Repisalud, 2011)
Dentigerous or follicular cyst is a benign odontogenic cyst is related to the crown of unerupted teeth with the highest percentage of incidence in third molars, canines and supernumerary teeth which can be found in ectopic positions in the upper jaw are located preferably in the maxillary sinus. We report a case of dentigerous cyst associated with a left upper third molar into the maxillary sinus in a female patient 19 years old who is sent to the Oral Diagnosis Clinic at the School of Dentistry Course Funorte-Brazil. In the same way we made a literature review of this pathological entity, their clinical characteristics, treatment and prognosis.
Dentigerous cyst associated with an ectopic tooth in the maxillary sinus: A report of one case and review of the literature
Keywords: Dentigerous cyst; Maxillary sinus; Unerupted tooth